Does healthcare consumerism serve as a barrier or facilitator to the implementation of value-based primary care? Strategies to promote synergy and success - Rangachari, Pavani (Frontiers in Medicine, 2023)
Value in health care is described as the measured improvement in a patient’s health outcomes for the cost of achieving that improvement. Primary care is often viewed as the foundational cornerstone for implementing value-based care. However, in the United States, primary care is also considered ground-zero for the rise in healthcare consumerism. In essence, consumerism refers to increasing expectations from patients (consumers) to be more active participants in decisions related to their healthcare. While much of the literature has portrayed the rise in consumerism as a barrier to the implementation of value-based primary care, some have argued that it may have potential to synergize with and facilitate the implementation of value-based primary care. This paper applies an enhanced stepwise implementation framework for value-based (equitable) care, to examine the potential for conflict and synergy between consumerism and value-based care in the emerging retail model of primary care. The application is based on potential actions of four key stakeholder groups: 1) retail healthcare entities, 2) primary-care providers, 3) consumers (patients), and 4) healthcare payers. The analysis helps to articulate the responsibilities of each stakeholder group in ensuring synergy between consumerism and value-based primary care. In addition, it helps to identify three drivers of synergy between consumerism and value-based care: 1) trust in the patient-provider relationship, 2) connected consumer-centric technology solutions, and 3) value-based consumer-centric payment models. Overall, the application helps to articulate a comprehensive framework for implementing value-based care that incorporates both the principles of consumerism and active consideration for health equity.